PATIENT SAFETY CULTURE ASSESSMENT AMONG THE STAF OF THE ORAL DENTAL HOSPITAL - kusniati, retno; Arti, Dwi; Harniati, Etny (Universitas Aisyah Pringsewu, 2024)
Background: Patient safety is a vital component of hospital services and a step to improve the quality of services. Incidents that can harm patients not only originate from health workers who are competent in their field as implementers of health services but also from the management system of a health service agency. It is critical to assess a healthcare organization's current safety culture to build an effective safety culture. Information about staff safety-related beliefs and behaviors helps identify areas of weakness and strength to design and implement interventions aimed at improving safety culture. Objective: to determine the culture of patient safety among the staff of the Muhammadiyah University Semarang Oral Dental Hospital. Method: This research was conducted at the Muhammadiyah University Semarang Oral Dental Hospital with a cross-sectional approach. The population in this study was 77 who came from the medical services and support sector of RSGM Unimus. The sample calculation results showed that 65 respondents would be involved in this research. The steps taken are; determining research locations and preliminary studies, preparing research instruments, data collection, data processing, and analysis. Results: R average of total positive responses of twelve patient safety dimensions was 78.2%, ranging from 51.5% to 98.5%. No dimension has an average percent positive score of less than 50%. 33.3% of the average positive responses were in areas with the potential for improvement, while 66.7% were in areas of strength. Conclusion: This study displays a good patient safety culture in most dimensions of patient safety.